Characterization of charge trapping processes in fully-depleted UNIBOND SOI MOSFET subjected to γ-irradiation - Houk, Y.; Nazarov, A.N.; Turchanikov, V.I.; Lysenko, V.S.; Andriaensen, S.; Flandre, D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
An investigation of radiation effect on edgeless accumulation mode (AM) p-channel and fully-depleted enhancement mode (EM) n-channel MOSFETs, fabricated on UNIBOND silicon on insulatior wafers (SOI), is presented in the paper. Characterization of trapped charge in the gate and buried oxides of the devices was performed by measuring only the front-gate transistors. It was revealed that the irradiation effect on EM n-MOSFET is stronger than that on AM p-MOSFET. Radiation-induced positive charge in the buried oxide proved to invert back interface what causes back channel creation in EM n-MOSFET but no such effect in AM p-MOSFET has been not observed. The effect of improving the quality of both interfaces for small irradiation doses is demonstrated.